A process for producing biopesticide. - Lau, Wei Hong; Abdul Samad, Norani; Sajap, Ahmad Said; Abdul Kadir, Hussan (2005)

(untitled)
The presentation provides a process for producing granulovirus as a biopesticide. Granulovirus comprises of a single protein, granulin, which is embedded in a crystalline protein matrix known as occlusion body. It serves as the biological control agent aginst armyworm. The occlusion bodies cause infection in the cells lining on the midgut. The process according to the present invention comprising in vivo propagating of granulovirus in insect larvae, isolating of the virus from infected insects, and purifying the virus for use as biopesticide. The produced biopesticide may be used to control insect pests when formulated as an agricultural spray.